Increase in brain-derived neurotrophic factor expression in early crack cocaine withdrawal. (26th September 2013) - von Diemen, Lisia; Kapczinski, Flavio; Sordi, Anne Orgle; de Magalhães Narvaez, Joana Correa; Guimarães, Luciano Santos Pinto; Kessler, Felix Henrique Paim; Pfaffenseller, Bianca; de Aguiar, Bianca Wollenhaupt; de Moura Gubert, Carolina; Pechansky, Flavio
Abstract: Recent reports suggest that brain-derived neurotrophic factor (BDNF) could be a biomarker for relapse, drug craving and withdrawal severity. In particular, elevated BDNF levels among former cocaine users have been associated with higher rates of relapse in 90 d. However, no data are available on BDNF levels at baseline and during crack cocaine withdrawal. This study evaluated BDNF among crack cocaine users during inpatient treatment, before and after withdrawal, vs. healthy controls. Clinical correlates with changes in BDNF levels were also assessed. Serum BDNF was evaluated in 49 male crack users on the first and last days of hospitalization and in 97 healthy controls. Serum BDNF was assayed using a sandwich ELISA kit. BDNF levels were significantly lower upon admission when compared to controls, even after adjustment for age, length of inpatient treatment, number of crack rocks used in the last 30 d, years of crack use and interaction between the latter two variables. At discharge, BDNF levels between patients and controls were similar. Number of crack rocks used in the last 30 d and years of crack use were inversely correlated with the outcome. Our findings show that BDNF levels increase during early crack cocaine withdrawal, at an inverse correlation with number of crack rocks used in the last 30 d and years of crack use.